Pengaruh Harga, Fasilitas dan Aksesibilitas terhadap Keputusan Berkunjung Wisatawan ke Destinasi Wisata Gunung Puntang - Rio Septa Nugraha Pamungkas; Faizal Hamzah (Lembaga Pengembangan Kinerja Dosen, 2025)
Tourism plays a crucial role as a key sector supporting Indonesia's economic growth, particularly in West Java Province, home to a variety of attractive destinations. Mount Puntang, known for its natural beauty and rich historical significance, is one such destination. This study aims to analyze the influence of price, facilities, and accessibility on tourists' decisions to visit Mount Puntang. This study used a quantitative approach, involving 100 respondents selected using the Slovin formula from a visitor population of 131,452 in 2023. Data were collected through a questionnaire assessing the influence of three main variables: price, facilities, and accessibility on visiting decisions. The results showed that price had a significant negative influence on visiting decisions. This means that the higher the price offered, the less interest tourists would have in visiting. Conversely, the available facilities and accessibility to Mount Puntang showed a significant positive influence. This indicates that the better the facilities provided and the easier it is to access the location, the greater the interest tourists would have in visiting. The coefficient of determination (R²) test showed that price, facilities, and accessibility together influenced 97.9% of tourist decisions, while other factors only influenced 2.1%. These findings underscore the importance of adapting more competitive pricing strategies, improving facilities, and facilitating transportation access to increase tourist interest in visiting Mount Puntang. Therefore, to attract more tourists, destination managers must focus on improving the quality of facilities and accessibility and optimizing pricing strategies to suit the capabilities of the target market, especially tourists who prefer destinations with value beyond just natural beauty. Furthermore, it is crucial for destination managers to pay attention to promotional factors that can influence tourist decisions.